2013
DOI: 10.1108/bfj-07-2013-0195
|View full text |Cite
|
Sign up to set email alerts
|

Perceived value of pasta in Greece and Romania

Abstract: Purpose -This study aims to provide international pasta marketers with a better understanding of how consumers perceive product value, which enables them to create and deliver value. The effects of COO, price, and content on purchase intentions are assessed. Design/methodology/approach -Data were collected via the survey method in Romania and Greece. Using a random utility discrete choice model, the authors test five hypotheses. Findings -Overall, Romanian and Greek individuals are less likely to buy US pasta;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…In sum, the significant variations in the loss, gain and promotion effect as well as the moderating effects of IRP clearly suggest that managers should not neglect the price-quality relationship in price setting for new products. These results also provide evidence that the price-quality relationship should not be abandoned from pricing research for foods, as was proposed by Dumitrescu et al (2013).…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…In sum, the significant variations in the loss, gain and promotion effect as well as the moderating effects of IRP clearly suggest that managers should not neglect the price-quality relationship in price setting for new products. These results also provide evidence that the price-quality relationship should not be abandoned from pricing research for foods, as was proposed by Dumitrescu et al (2013).…”
Section: Discussionsupporting
confidence: 61%
“…It is important for researchers and managers to pay attention to heterogeneity because price effects are at risk of being misinterpreted when heterogeneity is ignored. In a recent study, for example, Dumitrescu et al (2013) detected a negative effect of price on purchase intentions. They ascribed this effect to consumers' price sensitivity and concluded that "in food settings, price may no longer be a quality sign" (p. 1529).…”
Section: Introductionmentioning
confidence: 96%
“…Dagevos and Ophem (2013) reveal the value contained in food also consists of several parts, including product, process, location and emotional values. Dumitrescu and Nganje (2013) explain the perceived value of paste food in the development of Zeithaml's value; the perceived value of pasta in Greece and Romania evolved into the original food aspects of a country, price, food content, nationality and gender aspects. Health value denotes the realisation of non-monetary value: H1.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 97%
“…A lot of consumers really care about their purchases, it is important for them that green products which they buy were accepted in their social surrounds. If a product execute poorly in terms of social approval, negative incident like disagreement or dissatisfaction are probably could happen (Keller, 2011;Chi, 2012;Zhuang, 2010;Ansar, 2013;Li, 2013;Dumitrescu, 2013;Mahesh, 2013;Szocs, 2012;Ng, 2013). Based on the discussion above it can be hypothesized that:…”
Section: Green Perceived Valuementioning
confidence: 99%